(untitled) (International Journal of Built Environment and Sustainability, 2025)
In developing countries, the high demand for residential real estate in urban areas surpasses the available supply, driving up market prices and leading many people to live in slums and squatter communities. Considering the inadequate information on this imbalance of market forces, this study examined the types of residential property available in the Kaduna property market, the residents’ patterns of settlement, and the factors that determine the demand for residential housing in the study area. The 67 registered estate surveying and valuation firms in the study area make up the study population. As a result, 50 out of the 67 distributed questionnaires were collected, yielding a response rate of 74.6%. Data collected were analysed using descriptive statistics. The result shows that among the six types of residential property identified in the study area, the residents mostly occupied tenement buildings and 3-bedroom bungalows with a 31.37% frequency rate each. The residential settlement pattern in the study area is along high-density areas (Kawo and Sabon-Tsha) that command low rent and low-density areas (Barnawa Government Reserved Area) where rent is on the high side. Among the six residential property demand determinant variables identified in the study area, it was revealed that household income, rent affordability, and population growth were rated to be statistically significant in increasing order of 3.0, 3.54, and 3.68, respectively. Meanwhile, the remaining three factors—inflation rate, interest rate, and change in household taste—were less statistically significant in decreasing order of 1.76, 1.72, and 1.26, respectively. The study recommends that to break the private sector’s monopoly on real estate investment, which currently dictates the quantum and quantity of housing available, governments should participate more in the housing supply, particularly in low-income housing. This will help to lower rent in the study area.